Tipologija prevojnih oblikoglasnih premen v praslovanskem oblikovnem sistemu - Šekli, Matej (Slavistična revija, 2012)
The article discusses the reflexes of Proto-Indo-European and Proto-Balto-Slavic morphonological ablaut alternations in the Proto-Slavic morphological system both from the synchronic and diachronic points of view. The synchronic perspective presents the typology of ablaut alternations in Proto-Slavic, i.e., their distribution as well as their morphological functionin the morphological system. The diachronic part determines the origin of Proto- Slavic ablaut alternations and changes of their function, in comparison with the Proto-Indo- European and Proto-Balto-Slavic state of affairs.
Keywords: glasoslovje; morphology; morphonology; oblikoslovje; Phonetic sciences; praslovanščina; prevoj; Proto-Indo-European vowel gradation; Proto-Slavic; Proto-Slavic language; samoglasnik; tipologija; vowel; word formation